2019
DOI: 10.1111/apt.15089
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of coffee consumption following liver transplantation for hepatocellular carcinoma in cirrhosis

Abstract: Background: Increasing evidence suggests that coffee consumption might protect against hepatocellular carcinoma (HCC) and liver cirrhosis-associated death risk. Caffeine is a natural antagonist to extracellular adenosine and exhibits experimental tumoricidal activity. Aim:To evaluate if coffee consumption has beneficial effects on HCC recurrence after orthotopic liver transplantation (OLT). Methods:Coffee consumption of patients before and after OLT for HCC was assessed and correlated with HCC recurrence. HepG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Delia Hoffmann group have identified the expression of Tryptophan 2,3-Dioxygenase expression in human hepatocellular carcinoma cells, which indicated that TDO might be an immunotherapeutic target in hepatocellular carcinoma [28]. Besides, caffeine has shown tumouricidal activity in HCC cells and was associated with decreased risk of HCC recurrence [29]. Quinone oxidoreductase1 (NQO1) transcription might be inhibited by promoter hypermethylation in HCC, which might be involved in HCC pathogenesis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Delia Hoffmann group have identified the expression of Tryptophan 2,3-Dioxygenase expression in human hepatocellular carcinoma cells, which indicated that TDO might be an immunotherapeutic target in hepatocellular carcinoma [28]. Besides, caffeine has shown tumouricidal activity in HCC cells and was associated with decreased risk of HCC recurrence [29]. Quinone oxidoreductase1 (NQO1) transcription might be inhibited by promoter hypermethylation in HCC, which might be involved in HCC pathogenesis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The coffee or caffeine consumption has many other effects on the liver and lung. We summarize these emerging findings in the Table 2 [6,28,29,30,31,32,33,34,35,36,37,38,39,40,41] and Table 3 [24,26,42,43,44,45,46,47,48,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Ratanamarno et al [5] reported that catechin (C, 6), epicatechin (EC, 7), epicatechin gallate (ECG, 8) and epigallocatechin gallate (EGCG, 9) in fresh C. arabica L. leaves. Chen et al identified delphinidin 3,5-diglucoside (10) and delphinidin 3-(6"-malonyl-glucoside) (11) in the young leaves of C. arabica L. [6] Besides the above mentioned constituents, flavonoids and their glycosides were also isolated from the leaves of C. arabica L., which were named as cyanidin-3-O-Glu (12), cyanidin-3-O-rutinoside (13), kaempferol (14), kaempferol-3-O-Glc (15), kaempferol-3-O-Glc-Hex-DeHex (16), kaempferol-3-O-Glc-Hex (17), kaempferol-3-O-Glc-(6''-Rha) (18), quercetin (19), quercitrin (20), isoquercitrin (21), rutin (22), hyperoside (23), quercetin-3-O-Glc-Hex-DeHex (24), quercetin-3-O-Glu (25), luteolin (26), patuletin (27), fisetin (28), myricetin (29) and apigenin (30). [6][7][8][9] Their structures are shown in Figure 2.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Ginsenoside Rb1 and trigonelline could prevent the development of diabetic renal lesions by regulating the expression of miR-3550 and further associating with the Wnt/β-catenin signaling. [24] Live protection activity Wiltberger et al [25] reported that coffee consumption is associated with a decreased risk of hepatocellular carcinoma recurrence and provides for increased survival following orthotopic liver transplantation. Multivariate analysis showed that coffee intake emerged as a major factor of hazard reduction for overall survival postoperative.…”
Section: Antioxidation Activitymentioning
confidence: 99%